Design and development of text extraction and retrieval using style of documents in web searching - Balan, S.; Ponmuthuramalingam, P. (International Journal of Engineering and Technology, 2017)
This research focuses on study and extraction of web pages and documents are returned from goggle search engine. The useful task of web is to exactly match the accurate information. That information are categorized into many ways such as manual, structured, semi-structured texts and images. Query Result Records (QRR’s) is used to extract the text information from the different type of documents. Data region is used to identify the actual segmentation step and the domain of documents contains suffix and prefix. Time compared to the existing pruning and other techniques are more efficient in manner. We analyze the different type of alignments in this paper and propose a new technique for alignment retrieval to find precision and recall evaluating the retrieval performance.